P141 IVOR LEWIS MINIMALLY INVASIVE ESOPHAGECTOMY FOR ESOPHAGEAL CANCER : IMPACT OF THORACOSCOPY ON POST-OPERATIVE MORBIDITY. (23rd November 2019) - Louis, Martin; Thibault, Voron; Vincent, Drubay; Marguerite, Messier; Clarisse, Eveno; Guillaume, Piessen
Abstract: The aim: of this study is to assess the impact of thoracoscopy versus conventional thoracotomy on postoperative and oncological outcomes in patients undergoing Ivor Lewis esophagectomy with laparoscopic gastric mobilisation for esophageal resectable cancer. Background & Methods: Esophagectomy for cancer is a complexe procedure associated with a high rate of mortality and morbidity 1, 2, especially respiratory, despite recent improvements in perioperative cares and advances in surgical techniques. Recently, minimally invasive esophagectomy has shown a benefit in decreasing postoperative respiratory complications in 2 randomized trials comparing firstly the hybrid approach (Ivor Lewis with laparoscopy and right thoracotomy) to the open approach (MIRO trial 3 ) and secondly the totally minimally invasive approach with cervical anastomosis (McKeown with laparoscopy and thoracospy) to the open approach (TIME trial 4 ). Few studies have focused on comparing specifically thoracosopic(TMIE) versus conventional thoracotomy approach(HYBRID) for intra-thoracic anastomosis. We performed a single-center retrospective study, including all patients undergoing either Ivor Lewis HYBRID or TMIE in our high-volume center between 2010 and 2019. The primary endpoint was major postoperative complications within 30 days (Dindo-Clavien grade≥III). Secondary endpoints included operative parameters, postoperative morbidity and mortality within 90 days and quality of oncological resection. Results: 498 patients were included, 440 underwent HYBRID and 58 TMIE. Ninety-six patients(19.3%) had major postoperative complication, 11 patients(19%) in TMIE and 85 patients(19.3%) in HYBRID. Anastomotic leak (AL) rate was significantly higher in TMIE (36.2% versus 10.8%, p<0.001). However AL in TMIE group were frequently less severe than in the HYBRID group (rate of AL type 2/3 respectively 23.8% and 50%;p=0.044). Respiratory complications were observed in 202 patients (45.9%) in the HYBRID group and in 14 patients (24.1%;p=0.002) in TMIE group, without significant difference in severe respiratory complications rate. The complete resection rate (R0 resection) (5.3% vs 3.7%) and the number of lymph nodes retrieved (25.26 vs 25.92) were comparable in both groups. Conclusion: The TMIE approach is burdened with a significant AL rate, probably related to an unreached learning curve, which mitigates the benefit of this approach to respiratory complications. The technical difficulty caused by intrathoracic anastomosis, whose modalities are not well-established, remains a major concern.